The Husbands-Wives Relation Model of Long Distance Marriage Farmer Households - Kismini, Elly; Wicaksono, Harto; Putri, Noviani Achmad (Universitas Negeri Semarang, 2018)
SomahÃ‚Â orientationÃ‚Â within family institutions shows that a father serves as the head of a family and a main worker of the family living together with his nuclear family has changed.Ã‚Â The changes are notÃ‚Â only in economic-social aspects, but also cultural aspects.Ã‚Â The change occurs as a consequence ofÃ‚Â Long Distance MarriageÃ‚Â (LDM) carried out by farmer families to meet their life needs. The studyÃ‚Â focused onÃ‚Â the relationship model between husbands and wives in the farmer families whose husbands work in the city temporarily. The study shows that keeping husbands out of the village does notÃ‚Â changeÃ‚Â much of theÃ‚Â construction of patriarchal culture and the ideology of familialism in Tanggulangin community. The construction of the role of men and women in the LDM farmer families stillÃ‚Â exhibits theÃ‚Â strong influence of patriarchal culture and familialism ideology that distinguishes the roles of men and women in the dichotomy of public and domestic roles as well as the patterns ofÃ‚Â senior-junior partnerÃ‚Â relationsÃ‚Â both at the theoretical and practical levels.Ã‚Â Meanwhile, in the aspect of income earning and decision making, the relational model that is built in LDM farmer families LDM also depicts strong influence of patriarchy and ideologiesÃ‚Â familialism.